Story Mapping in Teaching Writing Narrative Text - Yuliana Yuliana (Universitas Jambi, Magister Program of English Education Department, 2017)
The title of this research was Teaching Writing by Using Story Mapping Technique. The main objective was to improve the students’ writing achievement. Quasi-Experimental design was used in this research which population was the eleventh grader of SMA Muhammadiyah Pagaralam with the total number 254 students and the sample were 64 students which consisted of two classes taken by purposive sampling technique. The data were collected by using written test. The data were analyzed by using independent sample and paired sample t-test. The result showed that the students who were taught by using story mapping technique gained better improvement with the value of t-obtained was higher than critical t-table, in which 3,73>2,38 with the significant value 0,01 value in their writing achievement. It means that the alternative hypotheses (Ha) was accepted and the Null Hypotheses (Ho) was rejected. In short, the using of story mapping technique could improve students writing achievement. Keywords: Story Mapping Technique, Writing Achievement.